Hydroalcoholic extract of needles of Pinus eldarica enhances pentobarbital-induced sleep: possible involvement of GABAergic system - Fatemeh Forouzanfar; Ahmad Ghorbani; Hasan Rakhshandeh; Mahmoud Hosseini (Mashhad University of Medical Sciences, 2016)
Objective: Insomnia is accompanied by several health complications and the currently used soporific drugs can induce several side effects such as psychomotor impairment, amnesia, and tolerance. The present study was planned to investigate the sleep prolonging effect of Pinus eldarica. Materials and Methods: Hydroalcoholic extract (HAE) of P. eldarica, its water fraction (WF), ethyl acetate fraction (EAF) and n-butanol fraction (NBF) were injected (intraperitoneally) to mice 30 min before administration of pentobarbital. Then, the latent period and continuous sleeping time were recorded. Also, LD50 of P. eldarica extract was determined and the possible neurotoxicity of the extract was tested on neural PC12 cells. Results: The HAE and NBF decreased the latency of sleep (p